A trans locus causes a ribosomopathy in hypertrophic hearts that affects mRNA translation in a protein length-dependent fashion - Witte, Franziska; Ruiz-Orera, Jorge; Mattioli, Camilla Ciolli; Blachut, Susanne; Adami, Eleonora; Schulz, Jana Felicitas; Schneider-Lunitz, Valentin; Hummel, Oliver; Patone, Giannino; Mücke, Michael Benedikt; Šilhavý, Jan; Heinig, Matthias; et al. (Genome biology, 2021)
BACKGROUND: Little is known about the impact of trans-acting genetic variation on the rates with which proteins are synthesized by ribosomes. Here, we investigate the influence of such distant genetic loci on the efficiency of mRNA translation and define their contribution to the development of complex disease phenotypes within a panel of rat recombinant inbred lines. RESULTS: We identify several tissue-specific master regulatory hotspots that each control the translation rates of multiple proteins. One of these loci is restricted to hypertrophic hearts, where it drives a translatome-wide and protein length-dependent change in translational efficiency, altering the stoichiometric translation rates of sarcomere proteins. Mechanistic dissection of this locus across multiple congenic lines points to a translation machinery defect, characterized by marked differences in polysome profiles and misregulation of the small nucleolar RNA SNORA48. Strikingly, from yeast to humans, we observe reproducible protein length-dependent shifts in translational efficiency as a conserved hallmark of translation machinery mutants, including those that cause ribosomopathies. Depending on the factor mutated, a pre-existing negative correlation between protein length and translation rates could either be enhanced or reduced, which we propose to result from mRNA-specific imbalances in canonical translation initiation and reinitiation rates. CONCLUSIONS: We show that distant genetic control of mRNA translation is abundant in mammalian tissues, exemplified by a single genomic locus that triggers a translation-driven molecular mechanism. Our work illustrates the complexity through which genetic variation can drive phenotypic variability between individuals and thereby contribute to complex disease.
Keywords: Ribosome biogenesis; Animals; Ribosomes; Genetic variation; Translational efficiency; malá jadérková RNA; Complex disease; sarkomery; Mice, Knockout; myši knockoutované; Saccharomyces cerevisiae; Cardiomegaly; HXB/BXH rat recombinant inbred panel; Organelle Biogenesis; Mice; Gene Expression Profiling; Spontaneously hypertensive rats (SHR); RNA, Small Nucleolar; messenger RNA; ribozomální proteiny; stanovení celkové genové exprese; Rats, Inbred SHR; myši; Genetic Variation; RNA, Messenger; Sarcomeres; regulace genové exprese; Ribosome profiling; Cardiac hypertrophy; Male; iniciace translace peptidového řetězce; Rats, Transgenic; krysa rodu Rattus; Ribosomal Proteins; potkani inbrední SHR; ribozomy; trans QTL mapping; kardiomegalie; Quantitative Trait Loci; Gene Expression Regulation; zvířata; mužské pohlaví; lokus kvantitativního znaku; Mice, Inbred C57BL; Myocardium; biogeneze organel; genetická variace; myokard; Ribosomopathy; Rats; potkani transgenní; Peptide Chain Initiation, Translational; myši inbrední C57BL